Implementation of the Payroll Accounting Information System Through Cash Management System (CMS) In Improving Internal Control of the Payroll System at CV. XYZ Jember - Ronaldo Liputo; Mainatul Ilmi; Nurshadrina Kartika Sari (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
This research was conducted to analyze implementation Cash Management System (CMS) in supporting internal control of the payroll system at CV. XYZ. This research uses a descriptive qualitative method with a case study approach. This research uses in-depth interviews with each informant. The research results show that the implementation of the payroll accounting information system at CV. XYZ by using the application Cash Management System (CMS) has been implemented quite well because the company has implemented it in accordance with the components of Committee of  Sponsoring Organization of the Treatway Commission or COSO. And with the CMS application, the distribution or distribution of employee salaries becomes very efficient because there are features real time transaction where authorization can be done anywhere and at any time.